Growth and characterization of textured well-faceted ZnO on planar Si(100), planar Si(111), and textured Si(100) substrates for solar cell applications - Tsai, Chin-Yi; Lai, Jyong-Di; Feng, Shih-Wei; Huang, Chien-Jung; Chen, Chien-Hsun; Yang, Fann-Wei; Wang, Hsiang-Chen; Tu, Li-Wei (Beilstein Journal of Nanotechnology, 2017)
In this work, textured, well-faceted ZnO materials grown on planar Si(100), planar Si(111), and textured Si(100) substrates by low-pressure chemical vapor deposition (LPCVD) were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), and cathode luminescence (CL) measurements. The results show that ZnO grown on planar Si(100), planar Si(111), and textured Si(100) substrates favor the growth of ZnO(110) ridge-like, ZnO(002) pyramid-like, and ZnO(101) pyramidal-tip structures, respectively. This could be attributed to the constraints of the lattice mismatch between the ZnO and Si unit cells. The average grain size of ZnO on the planar Si(100) substrate is slightly larger than that on the planar Si(111) substrate, while both of them are much larger than that on the textured Si(100) substrate. The average grain sizes (about 10–50 nm) of the ZnO grown on the different silicon substrates decreases with the increase of their strains. These results are shown to strongly correlate with the results from the SEM, AFM, and CL as well. The reflectance spectra of these three samples show that the antireflection function provided by theses samples mostly results from the nanometer-scaled texture of the ZnO films, while the micrometer-scaled texture of the Si substrate has a limited contribution. The results of this work provide important information for optimized growth of textured and well-faceted ZnO grown on wafer-based silicon solar cells and can be utilized for efficiency enhancement and optimization of device materials and structures, such as heterojunction with intrinsic thin layer (HIT) solar cells.
Keywords: atomic force microscopy; cathode luminescence; scanning electron microscopy; silicon solar cells; transparent conducting oxide; X-ray diffraction; ZnO